Acute exudative paraneoplastic polymorphous vitelliform maculopathy in a patient with thymoma, myasthenia gravis, and polymyositis. Issue 3 (May 2022) - Yu, He; Ma, Xinyu; Tong, Nianting; Zhou, Zhanyu; Zhang, Yu
Importance: This is the first reported case of acute exudative paraneoplastic polymorphous vitelliform maculopathy (AEPPVM) in a patient with thymoma, accompanied by myasthenia gravis (MG) and polymyositis. Objective: To examine the pathogenesis of ocular disease in a patient with yolk-like fundus lesions and thymoma, MG, and polymyositis throughout the body based on clinical manifestations, diagnosis, differential diagnosis, and genetic testing to determine the appropriate treatment course. Design, setting, and participants: We describe a 63-year-old woman who presented to our tertiary medical center with a 3-month history of reduced visual acuity in both eyes. Concurrent fundoscopy revealed a 2.0 × 1.7-mm, unifocal, yellow, round vitelliform lesion in the macular region, surrounded by multifocal, shallow, yellow-white pockets of subretinal fluid. The patient's medical history included thymoma with thymectomy treatment, combined with pericardiectomy and postoperative radiotherapy (20 years prior), followed by a diagnosis of MG with suspect thymic association (15 years prior). Three years prior, the patient had been diagnosed with polymyositis related to paraneoplastic syndrome; 1 year prior, she had been examined for pleural thickening due to suspected metastatic tumor. Results: On her most recent follow-up visit at 3 months after initial diagnosis, the patient was stable with no clinically significant progression in ocular or systemic conditions.